THE IMPORTANCE OF THE CONCEPT AND MEANING OF PLACE IN TOURISM GEOGRAPHY - Ali Movahed; Kamran Jafarpour Gahlehteimouri, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The place is one of the most complicated issues in geographical studies. Place refers to both sides of human and physical geography. There is not clearly understand about the place and sometimes refer to local, area, point, region, and landscape. Tourism geography is about different human and physical characteristics that conduct groups of people to move to a specific place “tourism destination”. Therefore, tourist moves have tied to so many different geographical concepts, aspects, and meanings of place. Different places have different identity and geography searches for these uneven distributions of place. Rapid move from one place in the earth to another place is possible by advanced transportation systems. Hiding and destroying the function and meaning place behind space in geography will minimize the success of entire geographical studies in particular tourism geography. No matter how fast human be “speed” shortening “distance” and the “time” of trips faster than decades ago, but they have never been able to carry what are attached to place. The first question is, are we at the end of the real meaning of the place and does place losing the meaning. The second question is how the ability to move from one place to another place has changed the concept and meaning of the place. A library research method and process involve gathering appropriate information. This study aims to show how tourism geography in terms of formation, activity, and significance in shaping and reshaping the new meaning of the place. Also, the evolution of the meaning and function of place in the context of space.